Automatic Control in space : proceedings of the 8th IFAC Symposium, Oxford, England, 2-6 July 1979 - Munday, Charles Walter (IFAC conference proceedings., 1980)
Automatic Control in Space is a compendium of papers presented on the Eighth IFAC Symposium that took place in Oxford, England in July 1979.